The place in the story (a fringe at the end of the world) - عمران نور; لطفيّة برهم; فيروز عباس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research discusses the place in the story (A fringe at the end of the world) by the author Hassan M. Youssef, and illuminates the aspects of the spatial semantic radiations that charged the general atmosphere of the story by emphasizing the tendency of Hassan M. Youssef for nationalism and humanity, and his entry into the Arab social fabric, whose area expanded in a wide area that allowed it to generate a semantic focus that inspires looking forward to liberation. The place in the story of Hassan M. Youssef constituted an important part of the map of Arab fictional creativity, and a catalyst for delving into the thematic dimensions of spatial extension in the narrative achievement .